Pengaruh Konsep Diri dan Motivasi Berprestasi Terhadap Hasil Belajar Fisika Peserta Didik - Muhammad Amran Shidik (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[THE EFFECT OF SELF-CONCEPT AND ACHIEVEMENT MOTIVATION ON STUDENTS ‘LEARNING OUTCOMES]. The purpose of this research is to determine the effect of self-concept and achievement motivation on student learning outcomes. This research is included in quantitative research with the type of ex post facto causal research. The research instrument used was a closed questionnaire to measure the variables of self-concept and achievement motivation and a multiple choice test to measure student learning outcomes. The sample in this study were students of class XI IPA at SMA Negeri 1 Kaledupa, Kaledupa District, Wakatobi Regency, Southeast Sulawesi Province. After the data was obtained, it was analyzed with multiple linear regression analysis using the IBM SPSS 24 application. Based on the results of the research data analysis, it was concluded that there was an effect of self-concept and achievement motivation on student learning outcomes, this was based on the significance value obtained at 0.00 < 0.05. The magnitude of the influence of self-concept and prestigious motivation on learning outcomes is 84.4%, this is obtained based on the value of R Square after data analysis.